The Role Of Influencer Credibility And Electronic Word Of Mouth (E-wom) On Purchase Decisions Among TikTok Shop Users With Customer Trust As A Mediating Variabel - Nawang Kencana Dewi; Lusia Tria Hatmanti Hutami; Azwar Azwar (Universitas KH. Abdul Chalim Mojokerto, 2026)
The decline in public trust in social media influencers amid increasing shopping activity through TikTok Shop has given rise to a contradictory phenomenon in digital consumer behavior. This situation raises questions about the role of influencer credibility and electronic word of mouth in shaping purchasing decisions, as well as the importance of consumer trust as a link between the two. This study aims to analyze the influence of influencer credibility and electronic word of mouth on purchasing decisions with customer trust as a mediating variable. The study uses a quantitative approach with a survey method of 120 TikTok Shop users. Data analysis was performed using SEM-PLS. The results show that influencer credibility has a positive and significant effect on purchasing decisions and customer trust. Electronic word of mouth has a positive but insignificant effect on purchasing decisions, but a significant effect on customer trust. Furthermore, customer trust has a positive and significant effect on purchasing decisions and is able to mediate the influence of influencer credibility and electronic word of mouth. These findings confirm that consumer trust is a key factor in driving purchasing decisions on social commerce platforms.